Pinalia elata (Eriinae) - taxonomic and conservation assessments of a lesser-known narrow endemic orchid from Peninsular Malaysia - Besi, Edward Entalai; Jin, Ng Y.; Ghazalli, Mohd N.; Endot, Mohd R.; Perdan, Khairuddin (2023)
Pinalia elata is an attractive endemic species of Peninsular Malaysia, known from only six localities within the Titiwangsa mountain range where it is confined to montane vegetation. However, four of these localities are now threatened by anthropogenic factors, raising concerns about the ongoing survival of this endemic species in the wild. Despite efforts to understand the conservation status of Malaysian orchid species, there remains much work to be done, particularly for endemic species confined to remote and mountainous areas. Therefore, this paper provides a detailed morphological description, photographic illustrations for easy identification of the species, and a conservation assessment based on the IUCN Classification Criteria. Morphologically, P. elata can be easily distinguished from the other Pinalia species in Peninsular Malaysia by its erect inflorescences with well-spaced, closed flowers along the apical half, subtended by prominently large purplish-brown bracts. The flowers resemble buds with the labellum hidden by the petals and sepals. A preliminary risk-of-extinction assessment categorizes P. elata as critically endangered, CR A2acd C2a(i) D, according to the IUCN Red List Categories and Criteria.
Keywords: PINALIA ELATA -- MORFOLOGIA; PINALIA ELATA -- IDENTIFICACION; ORQUIDEAS -- MALASIA; PINALIA ELATA; PLANTAS ENDÉMICAS -- MALASIA